AGE ESTIMATION FROM EPIPHYSEAL UNION OF BONES AT ANKLE JOINT: A STUDY FROM CHHATTISGARH REGION (Journal of Forensic Medicine & Toxicology, 2019)
Evaluation of age of an individual using various methods is required for medico legal purposes in both civil & criminal matters. It is one of the most important parameters for human identification. Radiographic changes during epiphyseal union provide an important means to estimate the age of adolescent & young adult skeletons. This study aims to investigate the relationship between stage of epiphyseal union at ankle joint & chronological age in Chhattisgarh population (Central India). The study was carried out in 120 healthy subjects (55 girls and 65 boys) aging from 13 to 20 years. The obtained results from the radiographs revealed that the complete fusion of epiphysis of lower ends of tibia & fibula is seen at 15-20 years. Females were consistently developing epiphyseal union at a younger age than their male counterparts, with two years of difference. The results also suggest that the age of epiphyseal union is found to vary greatly all over the world indicating the need for separate standards of age of epiphyseal union for separate regions.
Keywords: Epiphyseal Union; Ankle Joint; Distal End of Tibia; Distal End of Fibula